High frequency oscillations in epileptic and non-epileptic human hippocampus during a cognitive task - Pail, Martin; Cimbálník, Jan; Roman, Robert; Daniel, Pavel; Shaw, Daniel J; Chrastina, Jan; Brázdil, Milan (Scientific reports, 2020)
Hippocampal high-frequency electrographic activity (HFOs) represents one of the major discoveries not only in epilepsy research but also in cognitive science over the past few decades. A fundamental challenge, however, has been the fact that physiological HFOs associated with normal brain function overlap in frequency with pathological HFOs. We investigated the impact of a cognitive task on HFOs with the aim of improving differentiation between epileptic and non-epileptic hippocampi in humans. Hippocampal activity was recorded with depth electrodes in 15 patients with focal epilepsy during a resting period and subsequently during a cognitive task. HFOs in ripple and fast ripple frequency ranges were evaluated in both conditions, and their rate, spectral entropy, relative amplitude and duration were compared in epileptic and non-epileptic hippocampi. The similarity of HFOs properties recorded at rest in epileptic and non-epileptic hippocampi suggests that they cannot be used alone to distinguish between hippocampi. However, both ripples and fast ripples were observed with higher rates, higher relative amplitudes and longer durations at rest as well as during a cognitive task in epileptic compared with non-epileptic hippocampi. Moreover, during a cognitive task, significant reductions of HFOs rates were found in epileptic hippocampi. These reductions were not observed in non-epileptic hippocampi. Our results indicate that although both hippocampi generate HFOs with similar features that probably reflect non-pathological phenomena, it is possible to differentiate between epileptic and non-epileptic hippocampi using a simple odd-ball task.
Keywords: dospělí; Female; hipokampus; mozkové vlny; Electrodes, Implanted; Neuropsychological Tests; Adult; mladý dospělý; ženské pohlaví; Epilepsy, Temporal Lobe; neuropsychologické testy; lidé; epilepsie temporálního laloku; kognice; Drug Resistant Epilepsy; Male; Brain Waves; refrakterní epilepsie; Young Adult; Cognition; implantované elektrody; Hippocampus; lidé středního věku; mužské pohlaví; elektroencefalografie; Middle Aged; Electroencephalography; Humans